King Charcoal Sdn Bhd / Ikhmal Firdaus Norhisyam ... [et al.] - Norhisyam, Ikhmal Firdaus; Rosmadi, Muhammad Daniel Haikal; Ahmad Sha’arani, Ahmad Zakir Azri; Mohammad Rohaizan, Muhammad Rafi Hakimi (2022)
Vision: The goal is to make Malaysia a more environmentally friendly country and to take all necessary efforts to safeguard our environment so that it does not go to waste. Company Background: Bamboo may be used for food, housing, and a variety of other purposes. Its rapid growth rate has made it a low-cost, sustainable, and efficient crop. We were affected by this situation and came up with a plan to transform bamboo into useful resources that would increase the sustainability of agriculture and food production, such as organic charcoal. Product: Organic bamboo charcoal provides several benefits over other materials, particularly in terms of source quality, because bamboo does not harm the environment or generate air pollution. It helps to boost the Ozone layer's air efficiency. Furthermore, our plan is to deal with the air pollution caused by common charcoal material, which might harm our ozone layers. Market: Our products are aimed towards a worldwide audience. Considering our bamboo charcoal is superior to other forms of charcoal, it will appeal to a global market. It plays a crucial role in agricultural productivity, with demand growing over time. Distribution Channel: Our bamboo charcoal is manufactured in a factory in Perak, Malaysia, and we distribute it all over the world